Зображення сторінки
PDF

The value of this fraction, when a = 0, is the same as that of

(€* – 6-1)

[merged small][ocr errors][ocr errors][ocr errors][merged small][merged small][ocr errors][ocr errors][merged small][ocr errors]

The value of u will in this case coincide with that of

[ocr errors][ocr errors][ocr errors][ocr errors][merged small][merged small][ocr errors][merged small][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][merged small][ocr errors][merged small][ocr errors][ocr errors][ocr errors][merged small][merged small][merged small][ocr errors]
[ocr errors][ocr errors][ocr errors][ocr errors]

or, multiplying numerator and denominator by 2 (x – a)),

2 (x a)} (x b)+ (x – a) (x – b)-+1

- (0 – a) (x + a)-!+ 1 The following process may frequently be applied with advantage to the evaluation of indeterminate fractions : “ If x = a cause the fraction to assume the form , substitute a + h for x in both numerator and denominator, and develop both according to powers of h; reduce the new fraction to its simplest form, and then make h = 0; the result will be the true value of the fraction.” It is easily seen that this includes the ordinary method of differentiation.

[merged small][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][merged small][merged small][merged small][ocr errors]
[merged small][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][merged small][merged small][ocr errors][ocr errors]

Since in this case u would be impossible if x were greater than a, assume x = a - h; the result is

(2a)
1+ 33 a'

, when h = 0,

"

[merged small][merged small][ocr errors][ocr errors][ocr errors]

Let x = 0 + h, or h; then, expanding the circular function by the formula

[ocr errors][ocr errors][merged small][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors]
[ocr errors]

1.2.3 TXC.

This is the sum of the series

1 1 1
12 + 2? + 2+ &c. to o.

There are other forms of functions which become indeterminate for a particular value of the variable, but these may generally be reduced to the form Thus, if u = P.Q, and if for x = a, P = 0, Q = oo, we have u = 0 xoo, which is indeterminate. But if we assume Q= , we have

e assume

[ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors]

Therefore, applying the rule for vanishing fractions,

P

P
U = a =

[ocr errors]

But if Q = 00 when x = a, all its differential coefficients will also be infinite, and u, taking the form , is still indeterminate unless the factor which becomes infinite should happen to divide out.

[ocr errors]
[ocr errors]

To determine the value of a function u = =, which becomes for æ = a, we assume P=p, Quà, so that u= = , when x = 0.

omes

[ocr errors]

so

[ocr errors]
[merged small][ocr errors][ocr errors][subsumed][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors][ocr errors]

But if P = 00, and Q = oo, for x = a, all their differential coefficients will also become infinite, and will still have the form . This reduction, then, will not give us the true value of the fraction unless some factor divide out, or we can find some relation, depending on the nature of the functions, between the new numerator and denominator which will enable us to trace the real value.

A function u = P - Q, which becomes co – co when x = a, can frequently be reduced to the form

DT ; for if P = 5 , and

[ocr errors][merged small][ocr errors][ocr errors][ocr errors][ocr errors]

and its value is to be found by the usual method.

De Morgan's Differential Calculus, p. 172.

[merged small][ocr errors][ocr errors][merged small][merged small][ocr errors][merged small][ocr errors][ocr errors][ocr errors][merged small][ocr errors][ocr errors][ocr errors][ocr errors][merged small]

Differentiating the numerator and denominator n times in succession,

n(n 1)...2.1

---- = 0, when x = 0,

[ocr errors]
[ocr errors]
[ocr errors]
[ocr errors]
[ocr errors]
« НазадПродовжити »